Analisis Pendapatan Usahatani Pepaya California Di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara - Rosari Patri Malliling Malliling; Grace A. J. Rumagit; Esry O. H. Laoh (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the income of California papaya farming in Talawaan Village, Talawaan District, North Minahasa Regency. This research was conducted from August to October 2021. The data collected in this study were primary data obtained from direct interviews with the famers using a questionnaires. Secondary data was obtained from the Talawaan Village Office and data from literature samples. Based on the results of research, the average income of California papaya farming was Rp. 10.188.686/ha in October 2021. Income earned from the average receipt of Rp. 13.671.329/ha minus the average explicit cost consisting of out of family labor costs, seedlings, fertilizers, kill up, equipment depreciation, and taxes of Rp. 3.482.643/ha. The results of the analysis of agricultural feasibility using the analysis of R/C ratio is 3,9 shows that it is feasible that value of R/C ratio > 1. Thus it is blunted that california papaya farming in Talawaan Village, Talawaan District, North Minahasa Regency deserves to be pursued.